Photography as Art - Art as Photography : zur Art 8 '77, Basel. - Maison de la Culture, Chalon-sur-Saôn; Fotoforum der Gesamthochschule, Kassel; Art Basel Basel 1977 (Kassel : Fotoforum Kassel, 1977)
Burkert, Heribert ; Katase, Kazuo ; Wilp, Charles ; H. Krauss, Rolf ; van Kempen, Wink ; Neusüss, Floris M.
Photography as Art - Art as Photography I : Maison de la Culture, Chalon-sur-Saône, 7. September bis 12 Oktober 1975 / Fotoforum der Gesamthochschule, Kassel, 7. Januar bis 8. Februar 1976 / Art 8 '77, Basel
boek